Effect of Probiotic on the Pax2 Gene Expression during Kidney Development in Mice Embryos - Saleh, Ahmed Hamad (American Journal of Biomedicine and Pharmacy, 2025)
Background & aim: At several stages of kidney and urinary tract development, Pax2 and Pax8 have become important participants in the urogenital system. Therefore, the aim of this work was to evaluate the effect of probiotic on the pax2 gene expression during kidney development in mice embryos. Materials & methods: 30 experimental animals (Swiss mice) were utilized, three month-aged and weight ranged between 16-19gm at period April 2025. An acidophilus plus capsule (Solgar, USA) contains lactobacilli culture that injected (intraperitoneal) as two doses: 9*106/0.1 ml CFU and 18*106/0.2 ml CFU during pregnancy and then the fetal kidneys of these two group compare with control in terms of histology and molecular aspect. Results: Microscopic examination of fetal kidneys in the probiotic 9*106/0.1 ml group showed normal structures. However, 9*106/0.1 ml group demonstrated greater development in the structure of the nephron compared to the control group. The number of glomeruli was greater and more rapidly developed, and the differentiation of the convoluted tubules was faster than in the control group. Furthermore, the capsule surrounding the kidney was better developed. Similarly, in the probiotic 18*106/0.1 ml group, the development of the nephrons was more pronounced than in the control group, and the differentiation of the convoluted tubules and the capsule surrounding the kidney was more distinct and clear. on the other hand, the finding showed that gene expression in studied groups, the mean of folding changes in control group was 0.9325. in 9*106/0.1 ml probiotic group folding changes was 0.9667. in 18*106/0.1 ml probiotic group folding changes was 1.021. The results showed non-significant (P=0.001) changes in gene expression between studied groups. Conclusions: its concluded that the use of probiotics improves kidney development in fetuses, as the nephrons and urinary convoluted tubules were more developed and differentiated compared to the control group and improved expression of the Pax2 gene in fetal kidneys.